Data Warehousing and Knowledge Discovery 12th International Conference, DAWAK 2010, Bilbao, Spain, August/September 2010. Proceedings - Bach Pedersen, Torben; Mohania, Mukesh K.; Tjoa, A Min.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 12th International Conference on Data Warehousing and Knowledge Discovery, DaWak 2010 held in Bilbao, Spain in August/September 2010. The 26 revised full papers presented were carefully reviewed and selected from 112 submissions. The papers cover a wide range of topics within cloud intelligence, data warehousing, knowledge discovery, and applications.
Data Warehouse Modeling and Spatial Data Warehouses -- Logic Programming for Data Warehouse Conceptual Schema Validation -- A Model-Driven Heuristic Approach for Detecting Multidimensional Facts in Relational Data Sources -- Physical Design and Implementation of Spatial Data Warehouses Supporting Continuous Fields -- Benchmarking Spatial Data Warehouses -- Mining Social Networks and Graphs -- Discovering Community-Oriented Roles of Nodes in a Social Network -- A Graph-Based Clustering Scheme for Identifying Related Tags in Folksonomies -- Frequent Sub-graph Mining on Edge Weighted Graphs -- Physical Data Warehouse Design -- & : A Methodology for Effectively and Efficiently Designing Parallel Relational Data Warehouses on Heterogenous Database Clusters -- Yet Another Algorithms for Selecting Bitmap Join Indexes -- Speeding Up Queries in Column Stores -- Dependency Mining -- Mining Non-redundant Information-Theoretic Dependencies between Itemsets -- Discovery and Application of Functional Dependencies in Conjunctive Query Mining -- Using Transitivity to Increase the Accuracy of Sample-Based Pearson Correlation Coefficients -- Business Intelligence and Analytics -- The NOX Framework: Native Language Queries for Business Intelligence Applications -- Experience in Extending Query Engine for Continuous Analytics -- Development of a Business Intelligence Environment for e-Gov Using Open Source Technologies -- Outlier and Image Mining -- A Fast Randomized Method for Local Density-Based Outlier Detection in High Dimensional Data -- Specialty Mining -- Region of Interest Based Image Categorization -- Pattern Mining -- Meta-learning for Post-processing of Association Rules -- A Relational Approach for Discovering Frequent Patterns with Disjunctions -- An Occurrence Based Approach to Mine Emerging Sequences -- Mining Closed Itemsets in Data Stream Using Formal Concept Analysis -- Data Cleaning and Variable Selection -- XML Data Fusion -- An Efficient Duplicate Record Detection Using q-Grams Array Inverted Index -- Modelling Complex Data by Learning Which Variable to Construct.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Database management; Data mining; Information storage and retrieval systems; Information systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Systems Applications (incl.Internet).; Data Structures; Information Storage and Retrieval; Computer Communication Networks